FRASE VERBAL UAB METO DIALEK MIOMAFFO: KAJIAN TIPOLOGI SINTAKSIS - viktorius feka; Selfiana Triyanti M. Ndapa Lawa; Christmas P Ate (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
This study aims to describe the forms of verb phrase of Uab Meto (UM) in Miomaffo dialect; and to determine the types of verb phrase of that language. The type of this study is descriptive-qualitative. The data of this study were gathered through interview, recording and note-taking techniques. There were two kinds of data used in this study, that is to say, primary and secondary data. Primary data were obtained through field studies (empirical research), while secondary data were obtained through literature studies. The data obtained was subsequently processed into a phonemic-orthographic transcription, and after that analyzed using the corresponding, split, and introspective methods. The results of this study showed that the verb phrase of UM has ruling constituents in the verb category, while the limiting constituents can be nouns, adjectives, adverbs, modals, aspects, verbs, and prepositions. First, the verb phrases of UM formed by verbs and nouns generally have the type of verb+object (VO) or modified-modifier. Second, the verb phrase of UM formed by the constituents of aspects, modals, and adverbs has two types, namely modifier-modified and modified-modifier. Third, the verb phrase of UM formed by the constituents of negation has a unique type, namely modifier-modified-modifier. Fourth, the verb phrase of UM formed by the adjective constituents only has one type, namely modified-modifier. Fifth, the verb phrase of UM formed by verbs also has different types, in which the subordinating verb phrase has the modified-modifier types, while the coordinating verb phrase has an equal relationship. Sixth, the verb phrase of UM is also derived from prepositional phrases which also have two types, namely modified-modifiermodifier, and modified-modifier.